Adolescent adjustment to maternal cancer: an interpretative phenomenological analysis (IPA). (20th August 2018) - Rodriguez, Leonor; Groarke, Ann Marie; Dolan, Pat; MacNeela, Padraig
Abstract : Purpose: As an Interpretative Phenomenological Analysis (IPA), the purpose of this paper is to provide an in-depth understanding of adolescent experiences of maternal cancer to identify the individual and contextual factors that shape adolescent experiences and evaluates the potential applicability of the Family Ecology Model to the illness context. Design/methodology/approach: This analysis is focussed on three female adolescents who completed semi-structured interviews, which were subjected to IPA. Maternal illness is a challenge for adolescents, which can be improved or undermined by their contexts. The analysis yielded three sub-themes: family structure, social supports, experiencing maternal cancer at a time of transition and the lasting impact of cancer. Findings: This study found that adolescent experiences of maternal cancer depend on their contexts from an ecological perspective the type and quality of adolescent interactions determine coping and adjustment. Maternal cancer can be difficult as adolescents are already facing specific developmental challenges. Future research can benefit from adopting an ecological perspective to further understand adolescent experiences to support adolescent that may be more vulnerable and benefit from additional supports. This is not a generalisable piece of research but it provides a very deep and detailed understanding of the impact of maternal cancer on adolescents' developmental course and determines how the complexity of their contexts can serve as a risk or a protective factor at this challenging time. Originality/value: This paper contributes to the body of research by providing a comprehensive understanding of adolescents facing maternal cancer. The Ecological Model supports the findings of this research and proves to be a good model to understand the complex interplay between adolescents and their environments when facing a difficult challenge like maternal cancer is.